ChemInform Abstract: Substituent Effects on the Structure of Hexacoordinate Carbon Bearing Two Thioxanthene Ligands. Issue 45 (14th October 2013) - Yamaguchi, Torahiko; Yamamoto, Yohsuke
Abstract Review: 38 refs.